Mosaic epidermolytic ichthyosis - case report - Marcela Sena Teixeira Mendes; Samara Silva Kouzak; Thaissa Araújo Aquino; Gustavo Henrique Soares Takano; Antonio de Padua Lima (Sociedade Brasileira de Dermatologia, 2013)
Epidermolytic ichthyosis is a rare autosomal dominant disease that manifests at birth with fragile blisters and erosions that evolve into hyperkeratotic lesions associated or not with erythroderma. When the disease is associated with a mutation in cytokeratin 1, it may be related to hyperkeratosis of palms and soles, but this is not usually found when cytokeratin 10 is mutated. The disease can present in a mosaic form, due to post zygotic mutation of the gene involved, constituting an individual formed by two populations of genetically distinct cells - one carrier of the mutation and the other without it. We report a case of mosaic epidermolytic ichthyosis diagnosed in a female patient.